(untitled) (Bioagro, 2025)
Cover stubble in the zero tillage system benefits weed control. However, the influence of different cover crops on their composition and diversity in cowpea cultivation is little known. This study investigates the phytosociology, diversity and equity indices, control, similarity and beta diversity of weeds in cowpea cultivation managed on different cover crops. The experiment was carried out in a completely randomized block design, in a split plot scheme, with four repetitions. The plots were made up of straw from cover plants: spontaneous vegetation (T1), brachiaria (T2), millet (T3), sunn hemp (T4), jack beans (T5), brachiaria+crotalaria (T6), brachiaria+pig beans (T7), millet+crotalaria (T8), millet+pig beans (T9) and black mucuna (T10). The subplots were made up of treatments with and without weeding. The species Tridax procumbens, Digitaria horizontalis and Digitaria insularis were the most important species in the phytosociological study. The treatments changed the number of individuals and the diversity and equitability indices. In weeding management, T6 and T8 coverage showed greater diversity, while T9 showed greater evenness. Without weeding, T2 and T6 had fewer individuals and greater diversity, however, T8 and T9 showed greater evenness. Cover crops showed differences in weed suppression efficiency in weed-treated areas. However, brachiaria cultivation stood out as one of the most efficient for controlling these weeds. The similarity and beta diversity of weeds varied between treatments.